2020
DOI: 10.1098/rsif.2019.0712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of burst release and sustained release of pioglitazone-loaded fibrous mats on diabetic wound healing: an in vitro and in vivo comparison study

Abstract: In order to provide more effective treatment strategies for the rapid healing of diabetic wounds, novel therapeutic approaches need to be developed. The therapeutic potential of peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist pioglitazone hydrochloride (PHR) in two different release kinetic scenarios, burst release and sustained release, was investigated and compared with in vitro and in vivo tests as potential wound healing dressings. PHR-loaded fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…Another advantage of controlled drug release is improved patient compliance due to less frequent drug administration. [ 41–43 ] Microneedles may be classified into three categories based on their release profiles: burst release, prolonged release, and on‐demand release. Rapid drug release from polymeric systems is coined “burst or instant release.” [ 44 ] This kind of release is necessary for applications such as analgesic delivery, when rapid release of a therapeutic agent is essential.…”
Section: Release Profile and Methods Of Tuning Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Another advantage of controlled drug release is improved patient compliance due to less frequent drug administration. [ 41–43 ] Microneedles may be classified into three categories based on their release profiles: burst release, prolonged release, and on‐demand release. Rapid drug release from polymeric systems is coined “burst or instant release.” [ 44 ] This kind of release is necessary for applications such as analgesic delivery, when rapid release of a therapeutic agent is essential.…”
Section: Release Profile and Methods Of Tuning Releasementioning
confidence: 99%
“…For therapeutic agents such as those utilized at the beginning of wound healing, an initial burst release offers almost instantaneous relief, which is followed by sustained release to accelerate healing. [ 41 ]…”
Section: Release Profile and Methods Of Tuning Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Besides, PPARγ agonists can also down-regulate the expression of TLR4 (Ji et al, 2009). Using Pioglitazone-loaded fibrous mats which are prepared from pioglitazone hydrochloride (PHR) on the wound of DM rats, it is found that both burst-release and sustained-release kinetics can down-regulate the expression of TNF-α and promote DW healing, but the sustained-release form is more effective in reducing PMNs infiltration and inflammation, promoting epidermal regeneration and fibroblast proliferation (Cam et al, 2020), Similarly, topically using GQ-11 (a partial/dual PPAR α/γ agonist) and Pioglitazone on the wound of DM mice can also downregulate IL-1β and TNF-α, promote DW healing (Silva et al, 2019). An in-depth understanding of the relationship between TLR signaling pathways and drug regulation targets, as well as the impact of different types of drugs on drug delivery and efficacy, can provide a feasible direction for the treatment of DW.…”
Section: Therapeutic Targeting Of Toll-like Receptor Signaling In Diabetic Woundmentioning
confidence: 99%
“…hyperglycemia, promotes a proinflammatory phenotype of macrophages. These macrophages, purposed with killing pathogens and removing damaged tissue, release pro-inflammatory cytokines such as tumour necrosis factor-α (TNF-α), interleukin-1 beta (IL-1β) and interleukin-6 (IL-6) at a sustained level, preventing the progression of the healing process and the consequent release of antiinflammatory cytokines and growth factors [4][5][6]. There has also been research investigating the persistent presence of cytokine precursors; such as Nod-like receptor protein (NLRP3) and caspase-1, in diabetic wounds disrupting the healing process [7].…”
Section: Introductionmentioning
confidence: 99%